2013
DOI: 10.1016/j.molimm.2012.10.038
|View full text |Cite
|
Sign up to set email alerts
|

Identification of avian RIG-I responsive genes during influenza infection

Abstract: Ducks can survive infection with highly pathogenic avian influenza viruses that are lethal to chickens. We showed that the influenza detector, RIG-I, can initiate antiviral responses in ducks, but this gene is absent in chickens. We can reconstitute this pathway by transfecting chicken DF-1 embryonic fibroblast cells with duck RIG-I, which augments their antiviral response to influenza and decreases viral titre. However, the genes downstream of duck RIG-I that mediate this antiviral response to influenza are n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 67 publications
(78 reference statements)
2
53
0
Order By: Relevance
“…Previous research showed that TLR3 plays a critical role in the expression of pro-inflammatory cytokines, such as IL-6 and IL-8 (Le et al, 2007). The activation of duRIG-I signaling induces the expression of downstream innate immune genes including Mx, PKR , and IFN -β (Barber et al, 2013). Since MDA5 is a strong inducer of antiviral molecules and pro-inflammatory cytokines such as IL-2, IL-6, IFN -α, and IFN -γ (Wei et al, 2014), the upregulation of cytokines and antiviral proteins expression might have stemmed from the activation of these receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research showed that TLR3 plays a critical role in the expression of pro-inflammatory cytokines, such as IL-6 and IL-8 (Le et al, 2007). The activation of duRIG-I signaling induces the expression of downstream innate immune genes including Mx, PKR , and IFN -β (Barber et al, 2013). Since MDA5 is a strong inducer of antiviral molecules and pro-inflammatory cytokines such as IL-2, IL-6, IFN -α, and IFN -γ (Wei et al, 2014), the upregulation of cytokines and antiviral proteins expression might have stemmed from the activation of these receptors.…”
Section: Discussionmentioning
confidence: 99%
“…There is both observational and experimental evidence that a variety of domestic and wild avian species produce specific hemagglutination-inhibiting and neutralizing antibodies against HA, although opinion is divided as to their efficacy and duration, and there are some mechanistic reasons (such as the existence of truncated variants of IgY among ducks) that could prevent certain species from mounting an effective immune response (41)(42)(43). Nonetheless, AIV prevalence tends to decline with age whereas seroprevalence increases (9,(44)(45)(46), suggesting that some form of functional, long-term immunity is acquired upon exposure.…”
Section: Discussionmentioning
confidence: 99%
“…6). We assessed immune activation using absolute transcript qPCR of two genes downstream of the RIG-I pathway, interferon-beta ( IFN -β) and myxovirus resistance gene 1 ( MX1 ) (Barber et al 2013). Expression of duck TRIM27.1 or TRIM27-L alone had no effect on the relative expression of IFN -β or MX1 in comparison to a control vector expressing glutathione-S-transferase (GST) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…TRIzol ® reagent (Invitrogen) was used to lyse and extract RNA from the adherent cells according to the manufacturer’s instructions. We used chicken DF-1 cells for these transfections because no duck cell line is available, and expression of endogenous chicken TRIM27.1 is low, and is not upregulated in our microarray data by signalling through RIG-I upon infection with either BC500 (0.54-fold change) or VN1203 viral infection (0.83-fold change) (Barber et al 2013). …”
Section: Methodsmentioning
confidence: 99%